Innovativeness as part of quality and excellence development in the Slovenian public administration (survey results 2007–2008) - Polonca Kovač; Barbara Leskovšek (Central European Public Administration Review)
The purpose of the study was (1) to investigate the trends in the development of excellence and innovativeness, or the use of the relevant tools, by comparing the situations of 2003, 2006 and (as projected) 2009 to one another, and against the approaches used in companies, and (2) to encourage the spread of awareness within the public administration of the importance of identifying and spreading good practices. We found that trends are taking the same direction, with the number of different tools and the frequency of their use – especially of the CAF (Common Assessment Framework) and EFQM (European Foundation for Quality Management) models, partly also the BSC (Balanced Scorecards), and of ISO standards – being on a continual rise, while the main systemic deficiencies are the inconsistent top-down policy of quality and excellence development, and the non-existent methodology for empirical evaluation of the effects produced by the use of those tools. The organisations are left to their own initiative, and support of the Government and the Ministries is only declarative. Innovativeness, unlike this, primarily entails gradual improvements in the ways in which work is done – in the first place from the client perspective –, which is mainly reflected by the estimated financial savings.